Comparison of Effectiveness of Topical Steroid Versus Systemic Steroid in Nasal Polypi - Muhammad Umar,Muhammad Arshad,Sadia Chaudhry,Zafar Ahmed (Journal of Rawalpindi Medical College, 2015)
Background : To compare the effectiveness of topical steroid and oral steroid in reducing size of polyps and improving patency of nasal air way. Methods: In this randomized controlled trial a total of 140 patients were taken with bilateral nasal polypi. They were divided in 2 groups. Group A (70 ) were given topical steroids and Group B (70) were given oral steroids. Patients aged above 15 years of both genders with bilateral nasal polypi of stage 2 and 3 were included. Anterior rhinoscopy was done with the help of head-light. Patency was noted of both nostrils using nasal speculum. Endoscopic staging was done at the same time. Size was assessed with rigid endoscope as it can diagnose small polyps in the middle meatus. Both groups were examined again in follow up by anterior rhinoscopy and then by endoscope to see the stage of polyps. Chi square test were applied for comparison of efficacy. p value ≤0.05 was considered significant. Results: Mean+SD of age (yrs) of patient in Group A and Group B were 43.71+10.756 and 42.77+12.238 respectively. Chi-square test was applied to compare the efficacy (right nostril and left nostril) in both the groups which was statistically significant (p-value 0.009 and 0.005) which showed that topical steroid was more effective than systemic steroid in treating nasal polyps. Conclusion: Topical steroid is significantly effective than systemic steroid in treating nasal polyps.